Tunable Narrow Linewidth Erbium-Doped Fiber Ring Laser Based on Saturable Absorber and Self-Injection Feedback - Fujun Xu; Xiaxiao Wang; Xiaobin Xu; Ningfang Song (IEEE Photonics Journal, 2024)
We demonstrate a tunable single-longitudinal-mode (SLM) narrow linewidth erbium-doped fiber (EDF) ring laser (EDFRL) in a cost-effective way. The laser incorporates an unpumped-EDF-based saturable absorber (SA) and a self-injection feedback loop for mode selection. The EDFDRL exhibits linear tunability of 12.57 pm/ $^{° }$ C from 15 $^{° }$ C to 45 $^{° }$ C with a maximum tuning range of 0.3664 nm. At a pump current of 200 mA, we achieve a SLM EDFRL characterized by a high OSNR of 75 dB and an ultra-narrow linewidth of 330 Hz. Furthermore, it shows an excellent wavelength stability, with a maximum fluctuation of only 11.23 pm.